HUKUM KELUARGA ISLAM DAN PENYELESAIAN SENGKETA WARIS PERSPEKTIF FIQH DAN HUKUM POSITIF: SUDI KASUS DI GAMPONG LAM BHEU KECAMATAN DARUL IMARAH KABUPATEN ACEH BESAR - Mahmud, Muhammad Salim; Hidayat, Taufiq; Amiruddin, Amiruddin; Jani, Rafsan; Rismayana, Rismayana (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The settlement of inheritance disputes in Gampong Lam Bheu faces significant challenges from the perspective of fiqh and positive law. From the fiqh side, the low level of public understanding of faraidh law and the dominance of local customs often cause conflicts in the distribution of inheritance. Meanwhile, from the perspective of positive law, the formal process through the Religious Court is faced with obstacles in the form of procedural complexity, costs, time, and lack of official documents. This study uses a qualitative approach with a case study design. The results of the study show that: 1). The Settlement of Inheritance Disputes from the Fiqh Perspective in Gampong Lam Bheu, Darul Imarah District, Aceh Besar Regency is that the settlement of inheritance disputes according to fiqh in Gampong Lam Bheu is carried out through deliberation based on Islamic law (faraidh) with the guidance of religious leaders. The practice often prioritizes family harmony even though sometimes it is not entirely in accordance with the provisions of faraidh. 2). Settlement of Inheritance Disputes from a Positive Legal Perspective in Gampong Lam Bheu, Darul Imarah District, Aceh Besar Regency is that in a positive legal perspective, dispute resolution refers to the Compilation of Islamic Law through the Religious Court if deliberation fails. This process is legal but is considered complicated, time-consuming, and costly, so it is often used as a last resort. 3). Obstacles in Settling Inheritance Disputes from a Fiqh and Positive Law Perspective in Gampong Lam Bheu, Darul Imarah District, Aceh Besar Regency are that the main obstacles include low understanding of faraidh law, inconsistent roles of religious figures, complex court processes, and lack of official documents, which often prolong conflict resolution.